(3eaGJjM GdLfGf heUGHjM GdLfGfs - (3GdHQShj GdMfaj, jYbhH Hf Ydj, J (B931 (3g` s ((3eMeO Hf LeGds)
(3ChdgG (B:s
(3MeOG def ef Ydi YHGOg HfYeI GdESdGe hHYO ajbhd jYbhH Hf SjO Ydj bO CWHb SdGWjf GdYdeGAYdi Cf GdYde aj CTQa GdUaGJ SjeG GdYdhe GdTQYjI hCf ef Hjf GdcJH TQYI GdESdGes
(3BNQgG (B:s
(3ddTjN GdEeGe CHj GdbGSe GdMSjf Hf GdeaVd GdTgjQ HQGZH GdCUagGfj aj TQM TGajI ddehdi GdaGVd GdeYQha HLGQHQOjs
(3aj Chdg agQS ddehVhYGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 8 / 201s
(3eYLe GdeDdajf(B: 4 / 130s
(3cTa GdXfhf(B: 2 / 1044s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs